Faktor Yang Berhubungan dengan Pengetahuan Perawat Tentang Syok Hipovolemik: Sebuah Narrative Review - Witjaksono, Galuh; Trisyani, Yanny; Emaliyawati, Etika (MAHESA : Malahayati Health Student Journal, 2025)
ABSTRACT Hypovolemic shock is a life-threatening condition resulting from loss of large amounts of blood or fluid, which requires immediate detection and treatment to prevent organ damage and death. Nurses’ knowledge of hypovolemic shock is essential to improve patient outcomes, especially in early recognition and intervention. This study aimed to explore the factors that influence nurses' knowledge about hypovolemic shock. This narrative review was conducted by identifying articles from two databases (PubMed and Cinahl) and Google Scholar. The keywords used were “Nurses OR Nursing AND Knowledge AND Hypovolemic Shock AND Factor OR Predictor”. Eight articles from various countries were analyzed using cross-sectional methods. The results showed that the level of nurses’ knowledge was influenced by age, education, work experience, and training that had been attended. Conclusion: Nurses’ knowledge of hypovolemic shock tends to be still lacking. This study suggests the need for increased access to continuing education and structured clinical training to strengthen nurses’ competence in managing hypovolemic shock, with a focus on simulation and clinical practice-based learning. Keywords: Hipovolemic Shock, Knowledge, Nurses  ABSTRAK Syok hipovolemik adalah kondisi yang mengancam jiwa akibat kehilangan darah atau cairan dalam jumlah besar, yang membutuhkan deteksi dan penanganan segera untuk mencegah kerusakan organ dan kematian. Pengetahuan perawat tentang syok hipovolemik sangat penting untuk meningkatkan hasil perawatan pasien, terutama dalam pengenalan dini dan intervensi. Studi ini bertujuan untuk mengeksplorasi faktor-faktor yang mempengaruhi pengetahuan perawat tentang syok hipovolemik. Narrative review ini dilakukan dengan mengidentifikasi artikel dari dua database (PubMed dan Cinahl) dan Google Scholar. Kata kunci yang digunakan adalah “Nurses OR Nursing AND Knowledge AND Hypovolemic Shock AND Factor OR Predictor”. Delapan artikel dari berbagai negara dianalisis dengan menggunakan metode cross-sectional. Hasilnya menunjukkan bahwa tingkat pengetahuan perawat dipengaruhi oleh usia, pendidikan, pengalaman kerja, serta pelatihan yang pernah diikuti. Pengetahuan perawat tentang syok hypovolemia cenderung masih kurang. Penelitian ini menyarankan perlunya peningkatan akses terhadap pendidikan berkelanjutan dan pelatihan klinis yang terstruktur untuk memperkuat kompetensi perawat dalam menangani syok hipovolemik, dengan fokus pada simulasi dan pembelajaran berbasis praktik klinis. Kata Kunci: Syok Hipovolemia, Pengetahuan, Perawat